Evaluasi User Experience Sistem E-Learning Menerapkan User Experience Questionaire - Wahyudi Ariannor; Siti Abidah (STMIK Banjarbaru, 2022)
The class implementation at the STMIK Banjarbaru college has been supported by the e-Learning application as a learning medium, but since the beginning of its use there has been no evaluation to ascertain whether the e-Learning system used has been running well or not, and the extent of user experience (UX) is not known to the e-Learning application. This study aims to measure the UX of e-Learning applications quantitatively using the User Experience Questionnaire (UEQ) technique, involving 313 respondents. UX measurement uses 26 elements categorized on 6 scales. Based on the test results of the benchmark data set in the New User category, the Novelty scale is below the average, while in the Old User category, 2 scales are obtained below the average, namely Attractiveness and Novelty. The Novelty scale affects the Attractiveness scale, so the Novelty scale is very important to pay attention to, so that users still feel comfortable using e-Learning applications even in a long period of use.Keywords: Analysis; Benchmark datasets; Novelty; AttractivenessAbstrak. Penyelenggaraan perkuliahan di kampus STMIK Banjarbaru telah didukung aplikasi e-Learning sebagai media pembelajaran, namun sejak awal penggunaannya belum dilakukan evaluasi untuk memastikan apakah sistem e-Learning yang digunakan telah berjalan dengan baik atau belum, serta belum diketahui sejauh mana pengalaman pengguna (User Experience/UX) terhadap aplikasi e-Learning tersebut. Penelitian ini bertujuan melakukan pengukuran UX terhadap aplikasi e-Learning secara kuantitatif menggunakan teknik User Experience Questionnaire (UEQ), melibatkan 313 responden. Pengukuran UX menggunakan 26 elemen yang dikategorikan dalam 6 skala. Berdasarkan hasil uji set data benchmark pada kategori Pengguna Baru diperoleh skala Kebaruan (novelty) berada di bawah rata-rata, sedangkan pada kategori Pengguna Lama diperoleh 2 skala di bawah rata-rata, yaitu Daya Tarik (attractiveness) dan Kebaruan. Skala Kebaruan berpengaruh terhadap skala Daya Tarik, sehingga skala Kebaruan sangat penting untuk menjadi perhatian, agar pengguna tetap merasa nyaman menggunakan aplikasi e-Learning walau dalam jangka waktu penggunaan yang lama.Kata Kunci: Analisis; Set data benchmark; Kebaruan; Daya tarik